A Conceptual Analysis Of War In Thucydides And Hobbes - Rendeci, Ayten Tuana (Institute of Social Sciences, 2019)
War has been and remains a central phenomenon in human relations. When we first start to investigate the causes of the war, the process inevitably leads us to understand and work. Thucydides' History of the Peloponnesian War, which is the oldest reference source in the history of international relations, is my main text in this study and I evaluate the elements that build the war. Hobbes, a good reader of Thucydides, emphasized the founding nature of the war and the current wars and the war, which is also likely to live, were evaluated in the light of conceptual and theoretical analyses. The thesis is based on the fact that human emotions are at the forefront as the causes of war and that the war imposes its own system on human beings since the beginning of the war. In this study, the order-building feature of war proceeds again based on the fact that it is highly compatible with human nature.

Savaş insan ilişkilerinde merkezi bir olgu olmuştur ve olmaya da devam ediyor. Savaşı başta nedenlerini anlamak üzere araştırmaya koyulduğumuzda süreç bizi insanı anlamaya ve çalışmaya yöneltiyor kaçınılmaz olarak. Uluslararası ilişkiler tarihinin en eski referans kaynağı olan Tukidides' in Peloponnez Savaşı eseri bu çalışmadaki temel metnim olup, savaşı inşa eden öğeleri değerlendirmekteyim. İyi bir Thukides okuyucusu olan Hobbes'un savaşın kurucu niteliğine olan vurgusu ile günümüz savaşların ve yaşanma ihtimalinin de olduğu savaşın kavramsal ve teorik analizler ışında değerlendirmesi yapılmıştır. Tez, savaşın nedenleri olarak insan duygularının ön planda olduğu gibi, savaş başladıktan itibaren savaşın kendi sitemini insana dayatması üzerine şekillenmiştir. Yapılan bu çalışmada, savaşın düzen kurucu özelliği yine insan doğasına fazlasıyla uyumlu olmasına dayanarak ilerler.
Tukidides Ve Hobbes'ta Savaşın Kavramsal Bir Analizi
Thesis (M.A) -- İstanbul Technical University, Institute of Social Sciences, 2019
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Political Science; Siyasal Bilimler